# 4(3a+2)-5(6a-1)=2(a-8)-6(7a-4)+4a

## Simple and best practice solution for 4(3a+2)-5(6a-1)=2(a-8)-6(7a-4)+4a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 4(3a+2)-5(6a-1)=2(a-8)-6(7a-4)+4a equation:

4(3a+2)-5(6a-1)=2(a-8)-6(7a-4)+4a
We move all terms to the left:
4(3a+2)-5(6a-1)-(2(a-8)-6(7a-4)+4a)=0
We multiply parentheses
12a-30a-(2(a-8)-6(7a-4)+4a)+8+5=0

We calculate terms in parentheses: -(2(a-8)-6(7a-4)+4a), so:
2(a-8)-6(7a-4)+4a
We add all the numbers together, and all the variables
4a+2(a-8)-6(7a-4)
We multiply parentheses
4a+2a-42a-16+24
We add all the numbers together, and all the variables
-36a+8
Back to the equation:
-(-36a+8)

We add all the numbers together, and all the variables
-18a-(-36a+8)+13=0
We get rid of parentheses
-18a+36a-8+13=0
We add all the numbers together, and all the variables
18a+5=0
We move all terms containing a to the left, all other terms to the right
18a=-5
a=-5/18
a=-5/18

`